If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -5y + 15 = 0 Reorder the terms: 15 + 10x + -5y = 0 Solving 15 + 10x + -5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + 10x + -15 + -5y = 0 + -15 Reorder the terms: 15 + -15 + 10x + -5y = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 10x + -5y = 0 + -15 10x + -5y = 0 + -15 Combine like terms: 0 + -15 = -15 10x + -5y = -15 Add '5y' to each side of the equation. 10x + -5y + 5y = -15 + 5y Combine like terms: -5y + 5y = 0 10x + 0 = -15 + 5y 10x = -15 + 5y Divide each side by '10'. x = -1.5 + 0.5y Simplifying x = -1.5 + 0.5y
| 63/7= | | a=3a+1 | | 20.6=g-85.43 | | -2(x-4)=x+7 | | 7(-b+2)=9(-2b-17) | | 2(9-x)=6(x-8) | | 7n+(-1)/8=8 | | 3x-1-(1+2x)=1 | | 3.5w-35=w | | Sm=m(11+3m) | | -6m-10=88 | | 0.25(8w-4)=w+8-2w | | 3.5w-25=w | | 3.5w-25=w | | 2.094x=12 | | 6a+8x-8a+6ax-x= | | 6x+5(x-3)=-7 | | 11x+2=2(4x+1)-x+9 | | 50g=3g+(-552)+1g | | 54=(x*39.04) | | -4x+3(3x-5)=31 | | -4k+55=8k-29 | | -x+3+15x=-6+5x+54 | | (5ab)+(-9ab)= | | 136-7x=38x+16 | | -5-(3m+6)=-3(4m-2) | | 2.094x=4 | | 4-4x=-5 | | 11n=5n+36 | | 4(x+3)-x=-12 | | 180a=1.5 | | 54-12=64 |